Changing patterns of migration in Latin America: how can research develop intelligence for public health? - Baltica Cabieses; Helena Tunstall; Kate E. Pickett; Jasmine Gideon
Migration patterns in Latin America have changed significantly in recent decades, particularly since the onset of global recession in 2007. These recent economic changes have highlighted and exacerbated the weakness of evidence from Latin America regarding migration-a crucial determinant of health. Migration patterns are constantly evolving in Latin America, but research on migration has not developed at the same speed. This article focuses on the need for better understanding of the living conditions and health of migrant populations in Latin America within the context of the recent global recession. The authors explain how new data on migrant well-being could be obtained through improved evidence from censuses and ongoing research surveys to 1) better inform policy-makers about the needs of migrant populations in Latin America and 2) help determine better ways of reaching undocumented immigrants. Longitudinal studies on immigrants in Latin America are essential for generating a better representation of migrant living conditions and health needs during the initial stages of immigration and over time. To help meet this need, the authors support the promotion of sustainable sources of data and evidence on the complex relationship between migration and health.